(Ni NAPOSLEDOK(B... :s [(NSTIHI(B, (NPROZA(B] /s - (NqNICKAQ(B, (NtATXQNA gEORGIEWNA(B.s ((N~ERNOWCY (B:s [(NB(B. (NW(B.],s, 2023)
(NcE WVE P(B'(NQTA ZB)QÆRKA POETA(B-(NLÆRIKA tETQNI gEORGÆÇWNI qNICXKOÇ (B((NbORÆNOÇ(B). (NnOWA ZBÆRKA ^ERNÆWECXKOGO AWTORA SKLADAÃTXSQ Z TWORÆW(B, (NQKÆ WÆDOBRAV@TX ÇÇ DUMKI(B, (NROZDUMI Æ PEREVIWANNQ(B, (NROZKRIWAÃTXSQ ^UTTÃWA DU[A TA TREPETNE SWÆTOSPRIJNQTTQ(B, (NPOKAZANIJ BAGATIJ WNUTRÆ[NÆJ SWÆT WELIKOGO L@BLQ^OGO SERCQ(B. s)E
(NnA RUS(B. (NI UKR(B. (NQZYKAHs
Keywords: (NhUDOVNQ L)QÆTERATURAs)E -- (Nl)QÆTERATURA uKRAÇNIs)E -- (NpOEZ)QÆQs)E -- (NrOS)QÆJSXKOMOWNA(B.s)E; (NhUDOVNQ L)QÆTERATURAs)E -- (Nl)QÆTERATURA uKRAÇNIs)E -- (NpROZAs -- (NrOS)QÆJSXKOMOWNA(B.s)E; (N~ERN)QÆWECXKIJ AWTOR(B.s)E